Employer Perceptions of Study Abroad: Subverting or Supporting Labor Market Inequality? (Comparative & International Education Series, 2021)
Under the influence of neoliberalism, study abroad opportunities are often presented as an opportunity to gain a competitive advantage in the labor market. As access to study abroad is often limited by students’ socioeconomic status, growing participation may perpetuate unequal employment opportunities for graduates based on their backgrounds. Yet evidence on the function of study abroad in the labor market and its value to employers remains conflicted, varying markedly by case and context. This chapter compares employer perceptions of study abroad and its role in the labor markets of East Asia, Europe, and North America. For each of these world regions, the chapter examines the significance of study abroad experience in the perception of employers and the extent to which study abroad affects labor market opportunities.